Inter-rater Consistency Reliability of the Inertial Measurement Units as a Balance Evaluation Tool - Jang, Jeong-hee; Kim, Myung-chul; Park, Hang-sik; Kim, Hae-in; Paik, Jean-kyung (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study aim to evaluate the inter-rater consistency of static standing balance measurement equipment using inertial measurement system. Methods/Statistical analysis: 45 residents over 50 years old of Seongnam-si were recruited. The participants were randomly divided into 2 groups, and their static standing balance ability was measured by 2 physical therapists for 2 days. The measurements were performed on standing with open eyes, with closed eyes, standing on an unstable surface. The measured items were 3 parts, right and left trunk shaking, anterior and posterior trunk shaking, trunk rotation. Findings: For the open eyes part of the test, right and left trunk shaking’s Cronbach alpha was .552, and anterior and posterior trunk shaking’s Cronbach alpha was .626. And for the closed eyes part of the test, right and left trunk shaking’s Cronbach alpha was .409 and anterior and posterior trunk shaking’s Cronbach alpha was .623. Finally, for the unstable surface part of the test, only anterior and posterior trunk shaking data was able to be checked and the result was .570. The trunk rotation of all standing posture didn’t give significant Cronbach alpha data. Reliability of anterior and posterior trunk shaking in the all position was confirmed. And the right and left trunk shaking showed that there is reliability in the partly position. And there is no reliability in the trunk rotation of all standing position. Improvements/Applications: The results of this study shows the IMUs as a balance evaluation tool has moderate reliability in partial items.